Educational significances for concept of Wealth and children in the Holy Quran - Bakheet, Safiah Abdullah Ahmed; Alzhrani, Jawaher Abdullah; Alelyani, Khlood Ali; Altalhi, Safa Awad; Akram AlDeen, Aisha Abdullah (Journal of Educational and Psychological Sciences, 2023)
The aim of this research is to clarify the educational implications deduced from the term Wealth and children in the Holy Qur’an and to clarify the educational implications and matters of the hereafter, The research relied on the deductive approach, and the research concluded with several results, the most important of which are: 1- Wealth and children are a trial for the Muslim, a test for him, so that he can use them in obedience to God Almighty and getting closer to Him. 2- Wealth and children are considered an adornment from God by which he experiences worship and is not a value that indicates a person’s standing with God. Wealth and children are among God’s blessings if they are directed towards His pleasure, whether by earning or spending them. 3- The uselessness of Wealth and children on the Day of Resurrection if they are not used in obedience to God Almighty, and that it is a punishment for a person if he uses his Wealth and children in what God Almighty has forbidden. In light of the results, the following recommendations were made:- 1- Studying Wealth and children in the Prophetic Sunnah. 2- Studying the educational implications of pairing Wealth with acclamation in the Holy Qur’an. 3- Studying the educational contents of pictures of family relations in the Holy Qur’an. 4- Studying the patterns of children’s relationships with parents in the Holy Qur’an and its contemporary educational applications.